2018
DOI: 10.3892/mmr.2018.9511
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of BRCC3 exerts an anti‑tumor effect on cervical cancer in�vitro

Abstract: Cervical cancer is a serious malignancy that affects the health of females. In the present study, the association between breast cancer type 1 susceptibility protein/breast cancer type 2 susceptibility protein-containing complex subunit 3 (BRCC3) and cervical cancer was investigated. Reverse transcription-quantitative polymerase chain reaction and western blotting were performed to determine BRCC3 mRNA and protein expression levels in cervical cancer tissues and cells, in addition to the expression levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Previous studies have shown that silencing DEPDC1B in NSCLC suppressed cell migration and invasion in both NSCLC and cervical cancer cells. 10,13 Consistent with previous reports, DEPDC1B knockdown in PANC-1 and CFPAC-1 cells significantly inhibited cell migration and invasion. Yang et al demonstrated that ectopic expression of DEPDC1B in NSCLC enhanced cell migration and invasion.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies have shown that silencing DEPDC1B in NSCLC suppressed cell migration and invasion in both NSCLC and cervical cancer cells. 10,13 Consistent with previous reports, DEPDC1B knockdown in PANC-1 and CFPAC-1 cells significantly inhibited cell migration and invasion. Yang et al demonstrated that ectopic expression of DEPDC1B in NSCLC enhanced cell migration and invasion.…”
Section: Discussionsupporting
confidence: 90%
“…15 Previous results have proven that DEPDC1B plays a crucial role in cell growth, movement, differentiation, cell cycle progression and cytoskeleton reorganization. 15 Subsequent studies demonstrated that it is also overexpressed in other types of cancer, [8][9][10][11][12][13][14] and it is used as a prognostic factor that predicts outcomes in patients with non-small cell lung cancer 10 and prostate cancer. 11 In our present study, we show that the expression of DEPDC1B was obviously higher in PC cell lines than in normal human pancreatic ductal cell lines, which is similar to the results in non-small cell lung cancer 10 and cervical cancer 13 cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within several of the conserved MIGs identified herein, mutations have been linked to abnormal cell proliferation or cancer in humans. For example, mutations in BRCC3, which encodes a cell cycle regulator involved in G2/M phase transition, has been linked to myelodysplastic syndrome (MDS), as well as breast and cervical cancers (Boudreau et al 2007;Huang et al 2015;Zhang, Zhou 2018). Mutations in E2F3 have been associated with retinoblastoma, bladder and lung cancer (Ziebold et al 2001;Wang et al 2017a;Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%